2001
DOI: 10.1007/pl00013981
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of the Subterranean Mycelia and Ectomycorrhizae of Suillus grevillei Genets

Abstract: To analyze the distribution of subterranean parts of ectomycorrhizal genets, species-specific polymorphic markers are necessary. In this study, we examined the species-specificity of five polymorphic simple sequence repeat (SSR) markers of Suilus grevi//ei, and found that one, SG-5, is species-specific to S. grevi//ei and polymorphic. Using the SG-5 marker, we analyzed for the first time the horizontal and vertical distribution of the subterranean parts of several S. grevillei genets. The spatial distribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 18 publications
5
73
2
Order By: Relevance
“…Guidot et al (2001) employed the PCR-RFLP method using species-specific primer and demonstrated that the spatial distribution of genets of Hebeloma cylindorsporum sporocarps represented well that of ectomycorrhizas in the Pinus pinaster stands on both occasions that H. cylindrosporum formed fairy rings, and formed only small patches of a few sporocarps. Zhou et al (2001b) also revealed that the genet distribution of sporocarps reflected that of corresponding ectomycorrhizas for S. grevillei using a speciesspecific SSR marker. However, they also reported that the number of sporocarps was not always consistent with the size of the subterranean part of the genet, and sporocarps were not always centered over the subterranean parts.…”
Section: Relationship Between Genet Distribution Of Sporocarps and Ecmentioning
confidence: 85%
“…Guidot et al (2001) employed the PCR-RFLP method using species-specific primer and demonstrated that the spatial distribution of genets of Hebeloma cylindorsporum sporocarps represented well that of ectomycorrhizas in the Pinus pinaster stands on both occasions that H. cylindrosporum formed fairy rings, and formed only small patches of a few sporocarps. Zhou et al (2001b) also revealed that the genet distribution of sporocarps reflected that of corresponding ectomycorrhizas for S. grevillei using a speciesspecific SSR marker. However, they also reported that the number of sporocarps was not always consistent with the size of the subterranean part of the genet, and sporocarps were not always centered over the subterranean parts.…”
Section: Relationship Between Genet Distribution Of Sporocarps and Ecmentioning
confidence: 85%
“…Separation of root tips from soil samples is often done by sieving the samples (Guidot et al 2002;Landeweert et al 2003) or by the removal of root tips with a pair of forceps under a dissecting microscope (Chen and Cairney 2002;Dickie et al 2002;Landeweert et al 2003). In some cases complete hyphal strands and mycelium have been extracted from soil (Zhou et al 2001;H. Wallander, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…A genet refers to a group of sporocarps that have identical genetic backgrounds and resulted from the same mating event (Zhou et al 2000, 2001). Genet size differs among EM fungal species, ranging from a few metres to 100 m in diameter (Dahlberg 2001; Sawyer et al 2001).…”
Section: Population Geneticsmentioning
confidence: 99%